2019
DOI: 10.26434/chemrxiv.8796098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A X-ray Excitable Vibrational AIE System Based on Platinum (II) Salts

Abstract: Aggregation-induced emission luminogen excited by X-ray is highly advantageous for imaging and diagnosis but has not been achieved. Herein, we demonstrated BaPt(CN)4 as the first inorganic salt based AIE system which can be excited by X-ray. The AIE mechanism of BaPt(CN)4 is studied and the X-ray luminescence of BaPt(CN)4 is tested.understanding the unconventional clusteroluminescence of some non-conjugated luminescent system. More importantly, we found BaPt(CN)4 can be excited by X-ray, which fundamentally is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In 1853, G. G. Stokes reported that BaPt(CN) 4 exhibited bright green fluorescence in solid state but its solution looked like "mere water". [9] Unfortunately, the mechanism of this peculiar photoluminescence behavior had not been revealed. In addition to inorganic matters, some organic dyes with enhanced emission in the solid state have also been reported in the late 19th and early 20th centuries.…”
Section: Introductionmentioning
confidence: 99%
“…In 1853, G. G. Stokes reported that BaPt(CN) 4 exhibited bright green fluorescence in solid state but its solution looked like "mere water". [9] Unfortunately, the mechanism of this peculiar photoluminescence behavior had not been revealed. In addition to inorganic matters, some organic dyes with enhanced emission in the solid state have also been reported in the late 19th and early 20th centuries.…”
Section: Introductionmentioning
confidence: 99%